2009
DOI: 10.1021/jp9000169
|View full text |Cite
|
Sign up to set email alerts
|

Biosensing, Cytotoxicity, and Cellular Uptake Studies of Surface-Modified Gold Nanorods

Abstract: Herein we report biorecognition studies of protein IgG using biocomapatible gold nanorods as molecular probes. Surface modification of cetyltrimethylammonium bromide (CTAB)-stabilized gold nanorods was carried out by using poly(styrenesulfonate) (PSS) to reduce the toxicity of as-synthesized gold nanorods caused by free CTAB. ζ potential analysis confirmed charge reversal on the surface of gold nanorods caused by the PSS coating. Surface plasmon resonance exhibited by gold nanorods has been employed as a tool … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(86 citation statements)
references
References 39 publications
(64 reference statements)
2
83
0
1
Order By: Relevance
“…[28][29][30][31][32] For example, if CTAB is replaced by nonionic polyethylene glycol, the cytotoxicity is substantially reduced, but the cellular uptake drops as much as 94 %, and virtually no nanorods can enter the cells. [30] When polyelectrolytes are randomly wrapped around the CTAB bilayer, the uptake increases and the average number of rods that enter each cell ranges from hundreds [31] to one hundred thousand. [29] However, even polyelectrolyte-coated Au NRs are taken by cells in picogram quantities, which is only 0.1 % of a typical cell mass.…”
mentioning
confidence: 99%
“…[28][29][30][31][32] For example, if CTAB is replaced by nonionic polyethylene glycol, the cytotoxicity is substantially reduced, but the cellular uptake drops as much as 94 %, and virtually no nanorods can enter the cells. [30] When polyelectrolytes are randomly wrapped around the CTAB bilayer, the uptake increases and the average number of rods that enter each cell ranges from hundreds [31] to one hundred thousand. [29] However, even polyelectrolyte-coated Au NRs are taken by cells in picogram quantities, which is only 0.1 % of a typical cell mass.…”
mentioning
confidence: 99%
“…Nanostructures are efficiently taken up into cells, usually via the endosomal pathway through membrane fusion or receptor b-mediated endocytosis. Parab et al (2009) observed a shape-dependency of NP uptake as a result of a smaller contact area with cellmembrane receptors. Cells exhibit increased uptake of spherical particles in comparison with rod-or cylinder-shaped ones.…”
Section: Fluorochromesmentioning
confidence: 92%
“…This behavior is discussed in terms of a decrease in the cell-penetrating ability of PEG-coated nanorods [38]. However several authors [39,40] observed a considerable decrease in the cytotoxicity of nanorods not only after CTAB substitution with PSS, but also after triple washing, whereas rods without washing were rather toxic. Comparing this with addition of only free CTAB (without any particles) demonstrates that the action of triply washed AuNRs is approximately similar to that of 10 μm of free CTAB, while PSS-coated particles are analogous in toxicity to 1 μm of CTAB or to the control.…”
Section: On Biodecorated Gold Nanoparticles Distributed Within Tissuementioning
confidence: 98%